Avaliação da ocorrência e abundância de uma espécie invasora zooplanctônica em uma planície Neotropical : um estudo de longa duração. - Palazzo, Fabiana (2014)
The elucidation and understanding of biological invasion processes are fundamental due to the recurrent cases of invasive species in aquatic ecosystems and their potential effects on the structure and dynamics of aquatic communities. Studies on biological invasions include several steps, such as dispersion, biotic and abiotic factors. However, long term studies on this subject are lacking, especially with zooplankton organisms. The present study assessed the influence of biotic and abiotic factors on the biological invasion of a rotifer species (Kellicottia bostoniensis) in the Upper Paraná River floodplain, along a long time scale. As a first approach, we investigated the biotic resistance (species richness and abundance of zooplankton organism) on the occurrence of K. bostoniensis and examined the temporal pattern of its occurrence compared with rotifer species phylogenetically related and most abundant. The biotic resistance showed no effect on the occurrence of K. bostoniensis in the environments of the floodplain. Also, this species exhibited the same trend of occurrence over time of other rotifer species, and a different pattern in relation to other species, suggesting processes of coexistence and competition, respectively. In the second approach, we analyzed the occurrence and abundance of K. bostoniensis according to abiotic factors and temporal variability of these factors. Food availability, given by environmental variables, and smaller variations in environmental conditions have favored the occurrence and abundance of the invasive rotifer species over the time series. The invasion of K. bostoniensis was mainly determined by the amplitude of the flood pulse in this floodplain ecosystem, likewise the zooplankton community, and despite the low occurrence of K. bostoniensis during the study period, high abundances found indicate its invasive potential in environments of the Upper Paraná River floodplain.